The memory effect on fractional calculus: an application in the spread of COVID-19 - Barros, Laécio Carvalho de; Lopes, Michele Martins; Pedro, Francielle Santo; Esmi, Estevão; Santos, José Paulo Carvalho dos; Sánchez, Daniel Eduardo (Computational & applied mathematics, 2021)
Fractional calculus has been widely used in mathematical modeling of evolutionary systems with memory effect on dynamics. The main interest of this work is to attest, through a statistical approach, how the hysteresis phenomenon, which describes a type of memory effect present in biological systems, can be treated by fractional calculus. We also analyse the contribution of the historical values of a function in the evaluation of fractional operators according to their order. To illustrate the efficiency of this non-integer order calculus, we consider the SIR (susceptible–infected–recovered) compartmental model which is widely used in epidemiology. We employ this compartmental model to study the dynamics of the spread of COVID-19 in some countries, one version with memory and one without memory.